MICRO-CREDENTIALS AS A PREREQUISITE FOR THE PROFESSIONAL CAREER DEVELOPMENT OF EDUCATIONAL INSTITUTIONS GRADUATES (Innovative professional education, 2023)
The introduction of micro-credentials has become a distinctive feature of educational system development. Micro-credentials are elaborated to provide learners with specific knowledge, skills or competencies that meet social, cultural, personal educational needs, or labour market demands. Micro-credentials have their own niche in the professional qualifications system, as they are considered an important professional development tool that increased access to employment opportunities. Short-term learning, employment, labour market and competencies are key areas associated with micro-credentials.
Keywords: micro-credentials, short-term learning, employment, labour market, competencies